2002
DOI: 10.1007/s007920100224
|View full text |Cite
|
Sign up to set email alerts
|

A novel species of alkaliphilic Bacillus that produces an oxidatively stable alkaline serine protease

Abstract: A novel gram-positive, strictly aerobic, motile, sporulating, and facultatively alkaliphilic bacterium designated KSM-KP43 was isolated from a sample of soil. The results of 16S rRNA sequence analysis placed this bacterium in a cluster with Bacillus halmapalus. However, the level of the DNA-DNA hybridization of KSM-KP43 with B. halmapalus was less than 25%. Moreover, the G + C contents of the genomic DNA were 41.6 mol% for KSM-KP43 and 38.6 mol% for B. halmapalus. Because there were also differences in physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 25 publications
3
42
0
1
Order By: Relevance
“…Intriguingly, RepB also has lower, but significant, similarity to putative replication proteins from plasmids of gram-positive bacteria, i.e., 47% and 50% similarity to Rep43 of Bacillus sp. strain KSM-KP43 plasmid (28) and to Rep of pIP404 from Clostridium perfringens (8), respectively. The conservation in the RepB homologs is sustained over the N-terminal 380 amino acids, whereas the C termini of the polypeptides are variable (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, RepB also has lower, but significant, similarity to putative replication proteins from plasmids of gram-positive bacteria, i.e., 47% and 50% similarity to Rep43 of Bacillus sp. strain KSM-KP43 plasmid (28) and to Rep of pIP404 from Clostridium perfringens (8), respectively. The conservation in the RepB homologs is sustained over the N-terminal 380 amino acids, whereas the C termini of the polypeptides are variable (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The highest level of similarity at the amino acid level is the level of similarity with the putative replication protein (Rep43) from a cryptic plasmid found in Bacillus sp. strain KSM-KP43 (47). The Rep protein is also related to the replication protein encoded by plasmid pIP404 in Clostridium perfringens CPN50 (16) and to the nearly identical putative replication proteins (CTP1 and CTP45) encoded by Clostridium tetani plasmid pE88 (9).…”
Section: Resultsmentioning
confidence: 99%
“…strain KSM-KP43 (10). This protease also possesses the conserved methionine, but it resists oxidizing agents (10). Multiple amino acid sequence comparisons between KP-43 and related enzymes in the subtilisin family have indicated that KP-43 does not belong to any of the subfamilies of the subtilisin family (11).…”
mentioning
confidence: 99%
“…strain KSM-KP43 (10). This protease also possesses the conserved methionine, but it resists oxidizing agents (10).…”
mentioning
confidence: 99%